2006
DOI: 10.1080/10934520500349243
|View full text |Cite
|
Sign up to set email alerts
|

Hg(II) Exposure Exacerbates UV-Induced DNA Damage in MRC5 Fibroblasts: A Comet Assay Study

Abstract: When exposed to UVR, MRC5 fibroblasts incubated with mercuric chloride (0-15 microM) for 1 hour show increased DNA damage (as measured by the comet assay) compared to control cells (UVR irradiated but no mercuric chloride). This demonstrates that mercuric chloride and UVR in combination increase DNA damage in a synergistic manner. This may have implications to those exposed to mercury as it suggests that exposure to mercury in the environment may increase sensitivity to sunlight-induced carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…Our data support findings from previous studies, that nonlethal mercury exposure alone does not induce substantial DNA damage in either genome (Cebulska-Wasiewska et al 2005, Bradfield et al 2006). nDNA damage has been observed in some studies, but the weight of the evidence so far seems to support the hypothesis that compromising genetic damage may only occur at cytotoxic exposures (Cantoni and Costa 1983, Pieper et al 2014).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data support findings from previous studies, that nonlethal mercury exposure alone does not induce substantial DNA damage in either genome (Cebulska-Wasiewska et al 2005, Bradfield et al 2006). nDNA damage has been observed in some studies, but the weight of the evidence so far seems to support the hypothesis that compromising genetic damage may only occur at cytotoxic exposures (Cantoni and Costa 1983, Pieper et al 2014).…”
Section: Discussionsupporting
confidence: 93%
“…We did not observe increased damage in conjunction with UVC exposure, confirming a previous report (Cebulska-Wasiewska et al 2005), though elevated damage has been noted with UVA and also X-ray co-exposures (Cantoni and Costa 1983, Bradfield et al 2006). Collectively, these findings are consistent with one of mercury’s major proposed mechanisms of action, creating an environment sensitive to oxidative stress due to reduced antioxidant capabilities: H 2 O 2 , UVA, and X-ray exposures induce ROS generation, but UVC-induced ROS is very minor (Godar et al 1993, Agarwal and Sohal 1994, Hao et al 2004, Manda et al 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…by competing with ROSscavenging thiols (reviewed by Lo ´pez- Barea and Go ´mez-Ariza, 2006). Other authors have found genotoxicity induced by UV light to be enhanced by mercury (Bradfield et al, 2006). The link between genotoxicity and ROS led to many toxicological studies involving genotoxicity and oxidative stress-related biomarkers, such as lipid peroxidation (e.g.…”
Section: Introductionmentioning
confidence: 99%